Strategic Management of Education Based on Local Excellence in Indonesia - Herlina, Herlina; Anwar, Ade (Faculty of Economics and Business, Universitas Negeri Yogyakarta in collaboration with the Institute for, 2025)
The purpose of this study was to determine and examine the activities carried out in planning, implementation, evaluation, supporting factors, and obstacles in strategic management in schools based on local excellence. The lack of management capabilities indicates that the strategic management implemented in implementing local excellence-based education and how it is reflected in improving the quality of education that produces competent students with graduates who can be absorbed by the workforce. The method used in this study is a descriptive qualitative approach. The results of this study indicate that the efforts of the principal through program makers by referring to the school's vision, mission, and goals, the implementation of strategic management of Local Excellence-Based Learning such as increasing competence, empowering resources, fulfilling facilities and infrastructure, and establishing relationships with stakeholders, program evaluation, and supporting and inhibiting factors both from internal and external schools have shown good results, although not optimally.